Bioenergetic Performance of Bali Cows Employed in Ploughing Agricultural Land under Different Work Intensities - Lalu Wira Pribadi; Muhammad Ashari; Lalu Ahmad Zaenuri; Lukman H Y (Jurnal Biologi Tropis, 2023)
The study was undertaken to investigate the use of cow as draught power in soil cultivation of the different type of farming field namely paddy farming field and dry farming field. Ten cows (5 working pairs) were randomly selected from each location so that the total number of obsevation cows was 20 (10 pairs). From each location, 45 breeders were randomly selected as respondents, so that a total of 90 respondents was observed intensively. The results showed, that the main motives recorded from this study are all respondents (100%), both paddy field farmers and dry field farmers, raising cattle for a source of labor and for savings. Most of the farmers raise cattle also for the purpose of being a source of fertilizer (88% of respondents). Cows in dry field farming worked with heigher intensity then those worked on paddy field farming areas. Cows were employed in average 48 days/season and only 4 hours/day, each under 49,60 kg droaugt load, 45 HP draught power, and 45,57 kg draught force, which indicate that the use of cows as a draught animal power in soil cultivation at the transmigration site in the West Nusa Tenggara area is within sub maximal exercise.